Naturally derived cytokine peptides limit virus replication and severe disease during influenza A virus infection - Harpur, Christopher M; West, Alison C; Le Page, Mélanie A; Lam, Maggie; Hodges, Christopher; Oseghale, Osezua; Gearing, Andrew J; Tate, Michelle D (Clinical & translational immunology, 2023)
Objectives Novel host‐targeted therapeutics could treat severe influenza A virus (IAV) infections, with reduced risk of drug resistance. LAT8881 is a synthetic form of the naturally occurring C‐terminal fragment of human growth hormone. Acting independently of the growth hormone receptor, it can reduce inflammation‐induced damage and promote tissue repair in an animal model of osteoarthritis. LAT8881 has been assessed in clinical trials for the treatment of obesity and neuropathy and has an excellent safety profile. We investigated the potential for LAT8881, its metabolite LAT9991F and LAT7771 derived from prolactin, a growth hormone structural homologue, to treat severe IAV infection. Methods LAT8881, LAT9991F and LAT7771 were evaluated for their effects on cell viability and IAV replication in vitro, as well as their potential to limit disease in a preclinical mouse model of severe IAV infection. Results In vitro LAT8881 treatment enhanced cell viability, particularly in the presence of cytotoxic stress, which was countered by siRNA inhibition of host lanthionine synthetase C‐like proteins. Daily intranasal treatment of mice with LAT8881 or LAT9991F, but not LAT7771, from day 1 postinfection significantly improved influenza disease resistance, which was associated with reduced infectious viral loads, reduced pro‐inflammatory cytokines and increased abundance of protective alveolar macrophages. LAT8881 treatment in combination with the antiviral oseltamivir phosphate led to more pronounced reduction in markers of disease severity than treatment with either compound alone. Conclusion These studies provide the first evidence identifying LAT8881 and LAT9991F as novel host‐protective therapies that improve survival, limit viral replication, reduce local inflammation and curtail tissue damage during severe IAV infection. Evaluation of LAT8881 and LAT9991F in other infectious and inflammatory conditions of the airways is warranted. Novel host‐targeted therapeutics could treat severe influenza A virus infections, with reduced risk of drug resistance. Our studies provide the first evidence identifying LAT8881 and LAT9991F compounds, as novel host‐protective therapies that improve survival, limit viral replication and reduce local inflammation during severe influenza virus infection.